2007
DOI: 10.1590/s1516-35982007001000024
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for modelling energy and amino acid responses in poultry

Abstract: -The objective of this paper is to present some of the issues faced by those whose interest is to predict responses in poultry, concentrating mainly on those related to the prediction of voluntary food intake, as this should be the basis of models designed to optimise both performance and feeding programmes. The value of models designed to predict growth or reproductive performance has been improved inestimably by making food intake an output from, as opposed to an input to, such models. Predicting voluntary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
2
4
0
6
Order By: Relevance
“…The variations observed in the depositions of protein and fat in this study corroborate Leclercq (1998) and Gous (1998;2007), who state that increase in the limiting aminoacid concentration in the diet potentiates the deposition of protein and reduces fat deposition in broilers. Thus, reduction in the amount of fat in the carcass when higher lysine levels are used can be attributed to the increased energy expenditure for protein deposition and maintenance of greater muscle mass, providing a lower amount of energy for fat deposition (Leeson, 1995).…”
Section: Resultssupporting
confidence: 89%
“…The variations observed in the depositions of protein and fat in this study corroborate Leclercq (1998) and Gous (1998;2007), who state that increase in the limiting aminoacid concentration in the diet potentiates the deposition of protein and reduces fat deposition in broilers. Thus, reduction in the amount of fat in the carcass when higher lysine levels are used can be attributed to the increased energy expenditure for protein deposition and maintenance of greater muscle mass, providing a lower amount of energy for fat deposition (Leeson, 1995).…”
Section: Resultssupporting
confidence: 89%
“…Emmans (1981) suggested a 'maintenance unit' (BP m 0.73 .u) based on this theory. This scale has the added advantage of excluding body lipid from the unit of measurement: Expressing maintenance requirements on the basis of body weight or metabolic weight has been questioned because there is no demand for amino acids for the maintenance of lipid reserves (Emmans & Oldham, 1988;Burnham & Gous, 1992;Gous, 2007) which can vary considerably even among individuals with similar body weight (Emmans & Fisher, 1986;Emmans & Oldham, 1988;Burnham & Gous, 1992;Nonis & Gous, 2008). Thus, when comparing maintenance requirements between birds of different body weight and composition, body protein content of the bird at the time and in relation to its mature protein weight is preferred.…”
Section: Discussionmentioning
confidence: 99%
“…This causes the release of both amino and fatty acids from body reserves, leading to protein synthesis (Murray et al, 1998). If the above is true, then it can be speculated that in the current study, increases in dietary limiting amino acid concentrations may have increased protein synthesis and deposition (Gous, 2007) leading to improved yield in the breast meat and other carcass characteristics. Results from the present study agreed with the findings of Zhai et al (2016) who reported improved breast meat yield when the supplemental Lys and Met content of broiler diets were set at 120% and 140% of NRC requirements respectively.…”
Section: Discussionmentioning
confidence: 79%